Методика исследования миграции метана на дневную поверхность в пределах горного отвода ликвидированных шахт - Подрухин, А.А. (Физико-технические проблемы горного производства, 2007)
Проаналізована існуюча методика прогнозування виділення метану на земну поверхню. Пропонується доповнити методику шляхом проведення геодинамічних досліджень території гірського відведення. It is analysed existing methods of prognostication of selection of methane on an earthly surface. It is suggested to complement a method by conducting of geodynamical researches of territory of the mining lease.